Biological sulfate removal by Upflow Anaerobic Sludge Blanket (UASB) reactor - Simkhada, Sunil; Annachhatre, Ajit P.; Ishibashi, Yoshinobu; Eckhardt, Ing. Heinz; Asian Institute of Technology Partial Scholarship (Bangkok : Asian Institute of Technology, 1997)
Simultaneous anaerobic COD and S04 removal were investigated in a lab scale UASB reactor. Synthetic wastewater was used as a feed with glucose as a carbon source. The reactor startup lasted for about 3 months and COD concentrations were maintained below 3000 mg/L while the COD to S04 ratio was maintained around 10 to 20: 1 most of the time during the startup. Process operation with COD as to S04 ratio of 20: 1, 10: 1 and 5: 1 suggested that the COD conversion was in the range of 55 to 70% and the COD removal declined marginally with the increase in organic loading rate, values within 15 - 25 kg COD/m,.3. d. S04 removal was always about 85% for all the three COD to S04 ratios. S04 removal showed a marginally increasing trend with respect to sulfate loading rate, however S04 removal efficiencies were always higher than 85%. For higher COD to S04 ratio, higher proportion of COD was converted into methane up to 18%of influent COD, while in the lower ratio of 5: 1, COD converted to methane was reduced to 13%. On the other hand at a higher value of COD as to S04 ratio of 20:1, lower COD upto 3% was utilized for S04 conversion and at lower value of ratio of 5:1, higher proportion of COD was utilized for conversion of S04, i.e., 13% of influent COD. The sulfide accumulation was found to be higher at lower COD to S04 ratio and at higher sulfate loading rates. Higher sulfide ion concentrations affected the methanogenic activities and accordingly biogas generation. The biogas generation reduced to a low value of about 0.7 Lid during the later phase of COD to S04 ratio of 5:1 from the average values ofl6 to 18 Lid during the ratios of 20: 1 and 10: 1.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Sewage -- Purification -- Biological treatment